The possibilities of combined heat and power production balancing large amounts of wind power in Finland. (15th March 2015) - Rinne, S.; Syri, S.
Abstract: We simulate Finnish future energy system with large amounts of CHP (combined heat and power) and wind power. The Nordic countries have ambitious wind power targets, which means a substantial need for balancing power. One third of electricity in Finland is produced by CHP, and a large amount of nuclear power is running constantly as base load. There is significant correlation in wind power patterns across a large geographical area in Northern Europe, so the interconnected networks don't solve the balancing problem completely. A precautionary principle is to have ability to balance the electricity production and consumption on a national level. CHP with thermal storages could be economical and technically easy option for balancing. This alternative has been largely neglected in European studies. We simulate future wind power by upscaling existing hourly data. The economically optimal storage size was here found to be from the current 0.3% up to 30% of the total annual heat demand, depending on the wind power share and carbon trade price. We find that the use of economically optimal thermal storage can increase CHP production by 15% in the case of wind energy providing 24% of the total electricity production in Finland. Highlights: Large wind power share necessitates heat storages in CHP (combined heat and power) systems. CHP with storages replaces condensing power and increases the system efficiency. Without storages the system efficiency decreases. High wind power share and emission trade price favour large storages. Optimal storage size is from current 0.3% of the annual district heat use to even 30%.